2015
DOI: 10.5110/jjseg.56.94
|View full text |Cite
|
Sign up to set email alerts
|

Composite Planar Fabrics Capable of Distinguishing Between Slip Surface Clay and Fault Gauge

Abstract: It is impossible to distinguish slip surface clay from tectonic fault gouge based on only geological observation of surface of a drilled core. Then, half cut drilled core specimens prepared based on the resin fixing method were used to observe the slip surface clay and fault gouges in high-quality drilled cores in the landslide located in the Chichibu Belt in the Shikoku Central Mountain Region. Borehole inclinometers have detected cumulative displacements in this landslide. The results revealed fine structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The combination of a thrust fault and high-angle faults can occur widely in accretionary complexes in island arcs and could provide favorable conditions for DGSD and large landslides. Wakizaka (2013) and Yamane, Yamada, Sengoku, Wakizaka, and Akamatsu (2015) showed that gravitational deformation coincides with sliding along tectonic thrust faults, by analyzing high-quality drilled cores from landslides in the Shimanto and Chichibu accretionary complexes in Japan. The Kawarabi thrust became the discontinuous plane of the DGSD areas before the large-scale landslides, so normal-fault displacement is expected to have occurred along the Kawarabi thrust, although evidence of this is not observed due to subsequent deformation within the crush zone.…”
Section: Role Of a Thrust And A High-angle Fault In A Large-scale Rmentioning
confidence: 99%
“…The combination of a thrust fault and high-angle faults can occur widely in accretionary complexes in island arcs and could provide favorable conditions for DGSD and large landslides. Wakizaka (2013) and Yamane, Yamada, Sengoku, Wakizaka, and Akamatsu (2015) showed that gravitational deformation coincides with sliding along tectonic thrust faults, by analyzing high-quality drilled cores from landslides in the Shimanto and Chichibu accretionary complexes in Japan. The Kawarabi thrust became the discontinuous plane of the DGSD areas before the large-scale landslides, so normal-fault displacement is expected to have occurred along the Kawarabi thrust, although evidence of this is not observed due to subsequent deformation within the crush zone.…”
Section: Role Of a Thrust And A High-angle Fault In A Large-scale Rmentioning
confidence: 99%